MEMAKNAI DEMOKRASI PANCASILA - Apiek Gandamana (Universitas Negeri Medan, 2017)
Abstract : Interpret Pancasila Democracy. Democracy is a political system that is currently used by almost all nations and countries in the world. The political system of democracy is not only used by liberal countries that are actually freed but the political system of democracy is also used by the communist state of the country that is leading togetherness or collectivity. Communist countries call the democracy they use is proletarian democracy or people's democracy. Different from our country Indonesia which embraces the political system of Pancasila democracy, where the value of the value contained in democracy must be based on the value of Pancasila value. In Pancasila democracy besides based on the value of Pancasila value, there are 10 pillars of democracy mandated by the founders of the nation. Keywords: Democracy, The Value Of Pancasila Abstrak : Memaknai Demokrasi Pancasila. Demokrasi merupakan sistem politik yang saat ini digunakan oleh hampir seluruh bangsa dan negara di dunia. Sistem politik demokrasi bukan hanya digunakan oleh negara-negara liberal yang memang menjunjung kebebasan tetapi ternyata sistem politik demokrasi digunakan juga oleh negara-negara berfaham komunis yang menjunjung kebersamaan atau kolektivitas. Negara komunis menyebut demokrasi yang mereka gunakan adalah demokrasi proletar atau demokrasi rakyat. Berbeda dengan negara kita Indonesia yang menganut sistem politik demokrasi pancasila, dimana nilai-nilai yang terkandung dalam demokrasi harus dilandasi oleh nilai-nilai pancasila. Dalam demokrasi pancasila selain dilandasi nilai-nilai pancasila, terdapat 10 pilar demokrasi yang diamanatkan oleh para pendiri bangsa (faunding fathers). Kata Kunci: Demokrasi, Nilai-nilai Pancasila